2010
DOI: 10.1007/s11423-010-9153-6
|View full text |Cite
|
Sign up to set email alerts
|

Improving self-regulation, learning strategy use, and achievement with metacognitive feedback

Abstract: Comprehension of science topics occurs when learners meaningfully generate relationships and conceptions about what they read. In this generation process, learners' cognitive and metacognitive regulation is one of the most critical factors influencing learning. However, learners are not always successful in regulating their own learning, especially in computer-based learning environments (CBLEs) where they are alone. Based on this rationale, the present study was designed to examine the effects of two scaffold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
1
17

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(124 citation statements)
references
References 39 publications
6
100
1
17
Order By: Relevance
“…Making annotations is considered a useful study practice (Lee et al, 2010;Marshall, 1997). Annotating behavior is also associated with indepth reading, which is important for college courses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Making annotations is considered a useful study practice (Lee et al, 2010;Marshall, 1997). Annotating behavior is also associated with indepth reading, which is important for college courses.…”
Section: Discussionmentioning
confidence: 99%
“…More complex annotation strategies-such as summarizing, paraphrasing, finding examples, and generating questions-contribute to metacognitive monitoring and feedback. These strategies can enhance learners' self-regulation, recall, and comprehension (Flavell, 1981;Lee et al, 2010;Leutner, Leopold, & Den Elzen-Rump, 2007), and improve learning when used in review (Kiewra et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study focuses on metacognitive self-regulation because metacognitive processes are considered to be the most critical in self-regulation (Brockett & Hiemstra, 1991;Corno, 1986;Corno & Mandinach, 1983;Lee, Kim, & Grabowski, 2010).…”
Section: Internet Self-efficacymentioning
confidence: 99%
“…Various authors have reported positive effects on students' learning outcomes as a result of certain methods of providing feedback Lee, Lim, & Grabowski, 2010;Smits, Boon, & Sluijsmans, 2008;Wang, 2011). In other studies, no effects were found Corbalan, Kester, & van Merriënboer, 2009;.…”
Section: Computer-based Assessment For Learningmentioning
confidence: 99%